Thermo-responsive hydrogels with tunable transition temperature crosslinked by multifunctional graphene oxide nanosheets. (20th October 2017) - Wang, Yifan; Song, Chunpeng; Yu, Xinhong; Liu, Li; Han, Yanchun; Chen, Jing; Fu, Jun
Abstract: Hydrogels consisting of reactive monomers can respond to external stimuli, which is promising for many applications such as sensors, soft robotics, and actuators, etc . However, most of responsive hydrogels are hard to fabricate into smart devices due to their poor mechanical properties. In this paper, vinyl-modified graphene oxide (GO-VTES) nanosheets were facilely prepared through the coupling reaction between hydroxyl or carboxylic acid groups from graphene oxide (GO) and hydroxyl groups from hydrolyzed vinyltriethoxysilane (VTES). By using the multifunctional GO-VTES nanosheets as crosslinkers, N -isopropylacrylamide (NIPAM) and acrylamide (AAm) were copolymerized to generate a series of tough and thermo-responsive composite hydrogels. The structures and morphologies of GO-VTES were investigated by FTIR, Raman, XPS, XRD, AFM and TEM. The obtained thermo-responsive composite hydrogels exhibit enhanced mechanical properties, which can be tuned by varying the content of GO-VTES and AAm. Moreover, these hydrogels were thermo-responsive with the LCST tunable by manipulating the contents of GO-VTES and/or AAm in the hydrogels. This strategy to prepare responsive composite hydrogels with enhanced mechanical properties has attractive applications for fabricating smart soft actuators. Graphical abstract: